2014
DOI: 10.1080/10495398.2014.933741
|View full text |Cite
|
Sign up to set email alerts
|

In-vitroCharacterization and Evaluation of Apoptotic Potential of Bicistronic Plasmid Encoding HN Gene of Newcastle Disease Virus and Human TNF-α

Abstract: The viral gene oncotherapy in combination with cytokines emerges as an exciting strategy for cancer therapy due to its minimal side effects and tumor specificity. HN is the surface protein of NDV which is involved in virus infectivity and is known to kill many cancerous cell types. TNF-α, a multifactorial cytokine has direct anti-tumor activity by activating the extrinsic pathways of apoptosis. In the present study, HN gene of NDV and TNF-α of human were cloned at multiple cloning sites (MCS) 1 and 2 of bicist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…TNF-α has been recognized as an important host defense cytokine that affects tumor cells. One of the most prominent characteristics of TNF-α is that it is capable of functioning together with endothelial cells to cause apoptosis of tumor, resulting in tumor necrosis (Rajmani et al, 2015). The present results showed that the serum levels of IL-2, IL-6, TNF-α and IFN-γ were slightly restored and enhanced after PD treatment in a dose-dependent manner compared with those in the vehicle control group in H22 tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 44%
“…TNF-α has been recognized as an important host defense cytokine that affects tumor cells. One of the most prominent characteristics of TNF-α is that it is capable of functioning together with endothelial cells to cause apoptosis of tumor, resulting in tumor necrosis (Rajmani et al, 2015). The present results showed that the serum levels of IL-2, IL-6, TNF-α and IFN-γ were slightly restored and enhanced after PD treatment in a dose-dependent manner compared with those in the vehicle control group in H22 tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 44%
“…In our previous studies, we showed that the HN protein can cause apoptosis in chicken embryo fibroblasts and in HeLa cells [14,21]. We have demonstrated the activation of the SAPK/JNK pathway by HN [13].…”
Section: Discussionmentioning
confidence: 83%
“…HeLa cells are naturally resistant to TNF-a-induced cytotoxicity but may become sensitized when NF-jB transactivation is blocked or cells are treated with compounds that inhibit protein synthesis [20]. We proposed in the previous study that HN may also sensitize otherwise resistant HeLa cells to TNF-a by exerting an inhibitory effect on NF-jB activation through the accumulation of IFN-a [21]. With this perspective in mind, we assessed if HN protein could sensitize HeLa cells to TNF-a-induced cell death and if a combination of HN and TNF-a could exert a synergistic apoptotic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that the HN protein plays a critical role in the anti-tumor effects of NDV (10). HN hydrolyzes the surface sialic acid of the host cell, exposes biological recognition sites, and induces tumor necrosis factor-associated apoptosis-inducing ligand (TRAIL) expression at the surface of mononuclear cells in the host peripheral blood, and yet does so independently of viral replication (11,12). In addition, HN positioning in the tumor cell membrane also led to formation of identical recognition sites, which in turn improved the cytotoxic effects of the host immune system against tumor cells (13).…”
Section: Introductionmentioning
confidence: 99%